Sustainable Energy for An LED Lighting System Using Novel Control ‎Algorithm for Constant Power Regulation - Rajan , Dr. P. Soundar; Kuppapillai , Dr. Rajkumar; Prasanna , Dr. M. Arul; Kumar, Dr.Kevin K (International Journal of Basic and Applied Sciences, 2025)
A solar photovoltaic-driven interior LED lighting system is proposed in this ‎manuscript, which is applicable for clean rooms, laboratories, modular offices, ‎convention halls, theatres, churches, etc., during daytime as well as night hours. The ‎proposed scheme gets supply from the grid in the case of shortage/absence of solar ‎PV power. The power transfer from the PV source and the grid is customized to ‎utilize the maximum PV power to maintain the constant and required level of ‎illumination at the workplace. A Firefly algorithm, together with a conventional ‎proportional-integral (PI) controller, is designed and tested successfully for effective ‎power arrangement. The simulated and measured result shows the effectiveness of ‎the new approach‎.